TUTURAN NIRGENDER DALAM ACARA 13 TAHUN MATA NAJWA - Darma Putra, Agus; Yulia Kurnia Wahidah, Baiq (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
In the 13 Years of Mata Najwa program there were four types of nir-gender speech such as stereotypes, discrimination, patriarchy and marginalization. The four types of nir-gender speech is the result of social and cultural construction of society. This often happens, even though women always demand gender equality. Nir-gender speech at the 13 Years of Mata Najwa program is the focus of this research. This type of research is qualitative research with descriptive methods. Data collection techniques are carried out by recording and taking notes. Meanwhile, data analysis is carried out by interpretation, after describing the raw data and classifying the data. As for the results of this research, there are types of nir-gender speech such as: (1) unfortunately women are still often looked down upon (Stereotype); (2) I always ask, why does it seem like women are not allowed to have higher education than men (discrimination); (3) while men are required to have higher education (Patriarchy); (4) It seems that social construction also makes women's dreams very limited and narrow (marginalization).